The effect of laser epilation on recurrence and satisfaction in patients with sacrococcygeal pilonidal disease: a prospective randomized controlled trial - Demircan, Firat; Akbulut, Sami; Yavuz, Ridvan; Agtas, Huseyin; Karabulut, Koray; Yagmur, Yusuf (E-Century Publishing Corp, 2015)
Background: The primary aim of this prospective study was to investigate the effects of laser epilation on patient satisfaction and recurrence in patients who underwent pilonidal sinus surgery. Method: Sixty patients scheduled for pilonidal sinus surgery in our clinic between 2011 and 2012 were enrolled in this prospective randomized controlled study. Patients were divided in two groups of 30 patients each. Only the Karydakis flap reconstruction technique was performed in the first group. Two sessions of laser epilation were applied in the second group in addition to Karydakis flap reconstruction. The patients in the second group underwent laser epilation 2 weeks before and 3 weeks after the surgery for a total of 2 times in a private office. Results: There were no statistically significant differences between the groups in terms of age, gender, smoking usage, ASA Score, duration of patient's complaints, BMI and hospital stay. There were no statistically significant differences between the groups in terms of surgical site infection, wound separation, abscess formation at the any time postoperatively. There were statistically significant differences between the two groups in the first week post operation considering the VAS pain score (P<0.03) and VAS satisfaction score (P<0.01). While there were statistically significant differences between the two groups in the first month post operation considering the VAS pain score (P<0.0001), there were no statistically significant differences between the groups in terms of VAS satisfaction score in the first and three month postoperatively. In the telephone interviews done 1 year after the surgery, recurrence were detected in 4% of first group and in 20% of second group. Recurrence rates were significantly higher in the second group (P=0.045). Conclusion: Our results show that laser epilation does not reduce the relapse rates in pilonidal sinus surgery, as expected. It is obvious that prospective randomized studies need to be held on this subject.
Keywords: Pilonidal disease; laser epilation; recurrence; patient's satisfaction